'Vamos ver o que é possível': do acesso à empresa como campo de observação empírica - Coelho, J. V. (2017)
A crucial issue that researchers aiming to carry out in-depth qualitative case study research in organizational settings typically face, is the issue of gaining access. This involves both securing entry into the organization and ensuring that individuals will participate in the study as informants. Organizations are usually skeptical about the role of someone that is perceived as an outsider, its probably disruptive presence and discourse, and may not value academic studies. Organizational field access can also be difficult if the research focus is placed on topics that are perceived as sensitive. In addition, field access may be denied due to self-presentation issues: the way researchers provide information about the proposed study, and the specific value the study will provide to the organization. Researchers often spend a considerable amount of time on gaining and maintaining field access, but most do not seem to value this experience l analysis. The main goal of this paper is to share the experience of undertaking PhD qualitative fieldwork on two Portuguese multinational firms, in particular, the processes involved in gaining access to interview managers and employees involved in expatriation practices. Analytical work is supported in field notes that illustrate the most prominent issues involved in fulfilling the gaining access goal. Five factors are discussed as possible field access enablers, in qualitative organizational studies involving sensitive topics. We believe that the described research experience may benefit other qualitative researchers.